ANALISIS EFEKTIVITAS PROGRAM SAHABAT POHON DALAM MEMBANGUN KARAKTER DAN SIKAP PEDULI LINGKUNGAN SISWA SEKOLAH DASAR - Rahayu, Suwasti; Fitri Puji Rahmawati; Anik Ghufron (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
Increasingly complex environmental problems require an effective educational approach to build the character and attitude of environmental care from an early age. This study aims to evaluate the effectiveness of the Sahabat Pohon Program in building character and attitudes of environmental care in elementary school students, analyzing its impact, identifying factors that influence its effectiveness, as well as challenges and opportunities for its implementation. This research was conducted using descriptive qualitative method. Data collection was conducted using interview techniques, observation, and document analysis. The results showed that the Sahabat Pohon Program is effective enough in building character and environmental care attitudes, marked by an increase in ecological awareness, sense of responsibility, and pro-environmental behavior of students. Key success factors include direct experience with nature, curriculum integration, and community support. The main challenges include limited resources and curriculum integration, while the program opens up opportunities for the development of more comprehensive environmental education.